Clinical characteristics and outcomes of invasive Lomentospora prolificans infections: Analysis of patients in the FungiScope® registry. Issue 5 (15th April 2020) - Jenks, Jeffrey D.; Seidel, Danila; Cornely, Oliver A.; Chen, Sharon; van Hal, Sebastiaan; Kauffman, Carol; Miceli, Marisa H.; Heinemann, Melina; Christner, Martin; Jover Sáenz, Alfredo; Burchardt, Alexander; Kemmerling, Björn; et al.
Summary: Objectives: Invasive fungal infections caused by Lomentospora prolificans are associated with very high mortality rates and can be challenging to treat given pan‐drug resistance to available antifungal agents. The objective of this study was to describe the clinical presentation and outcomes in a cohort of patients with invasive L prolificans infections. Methods: We performed a retrospective review of medical records of patients with invasive L prolificans infection in the FungiScope ® registry of rare invasive fungal infections. Patients diagnosed between 01 January 2008 and 09 September 2019 were included in for analysis. Results: The analysis included 41 patients with invasive L prolificans infection from eight different countries. Haematological/oncological malignancies were the most frequent underlying disease (66%), disseminated infection was frequent (61%), and the lung was the most commonly involved organ (44%). Most infections (59%) were breakthrough infections. Progression/deterioration/treatment failure was observed in 23/40 (58%) of patients receiving antifungal therapy. In total, 21/41 (51%) patients, and 77% of patients with underlying haematological/oncological malignancy, had a fatal outcome attributed to invasive fungal infection. Combination antifungal therapy was frequent (24/40) and associated with improved survival. In particular, treatment regimens including terbinafine were significantly associated with higher treatment success at final assessment ( P  = .012), with a positive trend observed for treatment regimens that included voriconazole ( P  = .054). Conclusions: Lomentospora prolificans infections were associated with mortality rates of 77% and above in patients with underlying haematological/oncological malignancies and those with disseminated infections. While combination therapy is the preferred option for now, the hope lies with novel antifungals currently under development.